Effect of salinity changes on the midgut gland of Artemesia longinaris (Decapoda, Penaeidae) - Masson, Ignacio (2012)
The response of the midgut gland of Artemesia longinaris to salinity changes was evaluated by analyzing its histological changes. Animals were exposed gradually and abruptly to 33, 29, 25 and 16 psu for different time intervals and readapted to 33 psu for 30 days. Individuals maintained 10 days at 16 psu showed the lowest survival and presented histopathologies which were not present in those readapted to 33 psu. Shrimps abruptly transferred from 33 to 16 psu died in 3-5 h but did not show midgut gland alterations likely due to the brief exposure. Only shrimps abruptly transferred from 33 to 25 psu presented histopathologies after 96 h. When readapted to 33 psu for 30 days, the midgut gland recovered an unaltered structure. Except E-cells, which did not vary in height among treatments, F, R and B-cells were taller in animals gradually adapted to 29 than to 16 psu. Abrupt salinity changes had a significant effect on the mean height of F, R and B-cells of those animals transferred from 33 to 25 psu (from 24 to 96 h after transfer F and R-cells heights decreased, and from 96 to 144 h after transfer B-cells height increased). Our study shows the effect of osmotic stress at the tissue level on the midgut gland and, at least partially, explains the reason for the mortalities at low salinities.